Castle ghosts of the British Isles [videorecording (DVD)] - Hardy, Robert, 1925-2017 (Kultur ; Discovery Communications, Inc., 2009)
Features four complete programs that explore the legends, myths, and mystery of the haunted castles in England, Ireland, Scotland, and Wales. Castle Ghosts taps into the energies and aura of the supernatural.